Magnetic structure of synthetic akaganeite: A review of Mössbauer data - García, Karen Edilma; Barrero, Cesar Augusto; Morales, Alvaro Luis; Greneche, Jean Marc (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
The refinement of the Mössbauer spectra, i.e. the assignation of the correct number of spectral components and their physical origin, has been a long controversy in the case of akaganeite. Most interpretations are based upon the earlier reported tetragonal structure, and very few upon the recently reported monoclinic structure. On the other hand, the magnetic structure has been proposed to be collinear antiferromagnetic, speromagnetic or asperomagnetic. In this paper we critically revise some of the works that have been done to date and outline future experimental and theoretical studies required to gain a better understanding of the magnetic structure of akaganeite.